Design processes of graduation final papers in the academic units of the faculty of social sciences: regulations, progress and challenges - Araya Jiménez, Lisbeth (2014)
This article is one of the first material and concrete results of recent joint efforts made by the academic units of the Faculty of Social Sciences under the call of the Dean. The article in its first chapter reports current regulations governing the design, execution and presentation of Graduation Final Papers (GFP), at the second chapter concisely characterized academic training in research in general and the courses designed directly to support the process of preparing the GFP, the third section is a brief comparative analysis, concluding with the identification of the main strengths, weaknesses and challenges. The article ends with some alternative solutions to the challenges identified.